Efektivitas Amitriptilin dan Psikoterapi Kognitif dan Perilaku (Cognitive Behavior Therapy) Untuk Memperpendek Waktu Pemulihan Pasien Reaksi Kusta - Munthe, Celestinus Eigya (Jurnal Kedokteran Indonesia, 2009)
Background: A study on the effectiveness of amitriptyline and cognitive behavior therapy (CBT) toshorten healing time in leprosy reaction patients has been conducted at leprosy clinics RSK. SITANALAâ Tangerang, on the leprosy reaction patient in periods 1 September 2009 until 31 October 2009. Thisstudy aimed to determine the effectiveness of amitriptyline and cognitive behavior therapy (CBT) onshortening healing time in leprosy reaction patients.Methods: This studi was a randomized clinical trial. A sample of patients diagnosed as contracingtleprosy reaction was divided into three groups. One group received leprosy reaction standard therapyand amitriptyline 25 mg 3 times daily. Another group received leprosy reaction standard therapy,amitriptyline 25 mg 3 times daily, and cognitive behavior therapy. The third group received leprosyreaction standard therapy. Mean differences of the three groups were compared with ANOVAResults: The group with either standard therapy and amitriptyline or amitriptyline and CBT showedfaster rccovery period, as well as reduction in pain, sleep disorder, fever, rash, and depression. Provisionof CBT alone did not show significant improvement in these clinical presentation.Conclusion: Provision of CBT in conjuction with amitriptyline and standard therapi can shorten recoveryperiod, as well as reduce pain, sleep disorder, fever, rash, and depression, more than standard therapyalone. Sole provision of CBT without amitriptyline in conjunction to standard therapy does not showsignificant improvement in these clinical presentation.Keywords : amitriptyline, leprosy reaction, standard therapy, cognitive behavior therapy